Crossplay Reconfigures Gender Meaning in Contemporary Cosplay Culture: Crossplay Mengubah Makna Gender dalam Budaya Cosplay Kontemporer - Muhammad Nauval At Thaariq; Ferry Adhi Dharma (Academia Open, 2025)
This study examines cosplay practices, particularly crossplay, within contemporary popular culture. General Background: Cosplay is a performative cultural practice where individuals embody fictional characters through costume, gesture, and roleplay. Specific Background: In Indonesian society, gender is shaped by patriarchal norms and binary constructions of masculinity and femininity, often generating resistance toward cross-gender performance. Knowledge Gap: Limited research conceptualizes crossplay as a systematic deconstruction of gender stereotypes grounded in Judith Butler’s performativity and Jacques Derrida’s deconstruction. Aims: This study explores how cosplay and crossplay renegotiate gender meaning beyond biological determinism. Results: Using a qualitative descriptive approach with in-depth interviews involving ten active participants, findings show that crossplay enables identity negotiation, coping with social pressures, skill development, and reinterpretation of gender as fluid and context-dependent. Despite offline stigma, digital platforms provide more inclusive spaces for expression and community support. Novelty: The study integrates performativity and deconstruction to frame crossplay as a symbolic practice that destabilizes binary gender oppositions. Implications: Cosplay represents a cultural arena that rearticulates gender stereotypes and broadens scholarly discourse on gender fluidity within cultural communication studies. Highlights: Participants Reinterpret Masculinity and Femininity Through Symbolic Performance and Role Immersion. Digital Platforms Create Supportive Arenas Compared to Offline Societal Reactions. Role-Playing Practices Facilitate Identity Negotiation and Resistance to Patriarchal Expectations. Keywords: Cosplay, Crossplay, Gender Stereotypes, Performativity, Deconstruction